Ovipositional Behaviour Preference of Oriental Fruit Fly, Bactrocera dorsalis Hendel (Diptera: Tephritidae) on Different Host Fruits - Salmah, Mohamed; Norhayati, Ngah; Mohammad Hailmi, Sajili (2018)
The oriental fruit fly Bactrocera dorsalis Hendel (Diptera: Tephritidae), is a polyphagous insect pest that gives severe damage to orchard fruits when the female adults lay their eggs into the fruits. However, the damage can be reduced by manipulating the behavior of this female insect. Thus, this study aimed to determine the ovipositional preference behavior of B. dorsalis on different host fruits. The experiment set up was laboratorybased ‘no-choice’ and ‘choice’ of oviposition preference behavior by the insect. The parameter recorded were the number of fruit visit, duration of fruit visit, number of attempted to oviposit, number of oviposition and duration of oviposition completed. Guava (Psidium guajava L), mango (Mangifera indica L.) and papaya (Carica papaya L.) were used as host fruits. In ‘no-choice’ experiments, the host fruits significantly influenced the number of fruit visit and duration of the visit by B. dorsalis female. The most visited fruit by B. dorsalis female was mango whilst papaya shows the longest duration of the host fruit visit by B. dorsalis. Although the characteristics of host fruits differs, the number and duration of oviposition by B. dorsalis shows no significant difference among the host fruits and no activity of oviposition was recorded on guava fruit. When given a choice, the duration of fruit visit and number of attempt to oviposit by B. dorsalis significantly differed among host fruits. However, the host fruits do not influenced the number of fruit visit, number of oviposition and duration of oviposition completed. However, guava fruit shows the egg oviposition activity by B. dorsalis females whilst no oviposition behaviour was observed on mango and papaya. Results obtained in this experiment will benefit the study of insect pest behaviour which then can be use in biological control program in order to reduce the agriculture damage.